Harvard Business Review on Manufacturing Excellence at Toyota - Authors (Harvard Business Press, 2008)
Few companies have so consistently inspired management best practices as Toyota. In everything from strategic operational design and quality improvement to integrated product development and management training, the company has achieved success through constant innovation. This collection shows just how Toyota does it--and how you can apply these same lessons to fuel success in your company.